Israel: Half a year under the Bennett government - Lidia Averbukh; Peter Lintl (Stiftung Wissenschaft und Politik (SWP), 2022)
From spring 2019 until summer 2021, Israel was politically paralysed because no stable government could be formed. Four elections were necessary before a new government took over on 13 June 2021. Not only was Benjamin Netanyahu replaced as prime minister after 12 years. A coalition was formed that covers almost the entire political spectrum. In the meantime, it has stabilised and its direction is becoming clearer. Nationally and internationally, the coalition has broken with the populist rhetoric of the Netanyahu government. At the same time, it is exploring different policies: Domestically, it is for the first time including an independent Arab party and has stopped the attacks on principles of liberal democracy. In its foreign policy, it is promoting rapprochement with the European Union (EU) and the Biden administration as well as more integration into the region. It is also trying to contain the conflict with the Palestinians through social and economic measures. But a political rapprochement is not in sight. A 'point of no return' is looming, making a two-state solution impossible.
Keywords: 320